The Copying Power of One-State Tree Transducers - Engelfriet, Joost (DAIMI Report Series, 1978)
One-state deterministic top-down transducers (or tree homomorphisms) cannot handle ''prime copying'', i.e. their class of output (string) languages is not closed under the operation L ( -> { (w)^f(n) | w in L, f(n) >= 1 } ) , where f is any integer function whose range contains numbers with arbitrary large prime factors (such as a polynomial). The exact amount of nonclosure under these copying operations is established for several classes of input (tree) languages. These results are relevant to the extended definable (or restricted parallel level) languages, to the syntax-directed translation of context-free languages and to the tree transducer hierarchy.